Implementasi Digital Promotion Bilingual untuk Meningkatkan Daya Saing UMKM Cahaya Pancing - Johny Budiman; Verni (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The development of digital technology requires MSMEs to adapt in order to increase their competitiveness and expand their market reach. Cahaya Pancing MSME, which is engaged in the sale of fishing equipment and supplies in Batam City, still relies on conventional marketing and has not made optimal use of digital media. This community service activity aims to help Cahaya Pancing SME build and optimize its digital presence through the implementation of a bilingual digital promotion strategy (Indonesian and English). The method used is a qualitative approach through interviews and field observations to identify the needs and problems of partners. Based on the analysis results, the design and implementation of outputs were carried out in the form of creating business emails, Instagram and Facebook social media accounts, business logos, Linktree, bilingual digital content, as well as assistance in content management and digital promotion. The results of the activity showed an increase in social media activity, customer interaction, improved Google ratings, and increased consumer trust and interest. The results showed measurable improvements, including active management of Instagram and Facebook accounts, increased engagement in terms of likes and comments, improvement in Google ratings, and higher customer interest reflected in increased inquiries.  This activity made a positive contribution to strengthening the digital identity, increasing the visibility of the business, and supporting the sustainability and competitiveness of Cahaya Pancing MSMEs in the digital era.